The Relationship Between the Length of Hemodialysis with the Level of Depression in Patients in the Hemodialysis Room - Mulyono, Ardy; Sunia A. A , I Gusti Made; Ganggur , Maria Sariwaty (Newinera Publisher, 2025)
Chronic Kidney Disease (CKD) stage 5 is a condition of chronic kidney function decline with GFR less than 15 mL/minute/1.73 m2 . CKD stage 5 requires renal replacement therapy either by transplantation or dialysis. Currently, the most common renal replacement therapy is hemodialysis. Hemodialysis is undergone by patients throughout their lives and is carried out in hospitals or hemodialysis centers. CKD patients stage 5 who undergo hemodialysis have many setbacks and limitations in their lives so that they are susceptible to depression. This study aims to determine the relationship between the length of time patients undergo hemodialysis and the level of depression. The design in this study was descriptive analytical with a cross-sectional approach with 31 respondents who underwent hemodialysis therapy at Ruteng Regional Hospital in September - October 2024. Depression data were taken using the Zung Self-rating Depression Scale questionnaire. Bivariate data analysis used the Spearman Rank test with a significant value at p-value <0.05. The Spearman Rank test showed a negative correlation between the length of time patients underwent hemodialysis and the level of depression with a p value = 0.002 (p <0.05) and a correlation coefficient (r = -.539) which showed that the longer the patient underwent hemodialysis, the lower the level of depression.